Reconstructing Islamic Religious Education Methodology through Instructional Technology to Strengthen Digital Ethics among Generation Z - Ahmad Shidiqi (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
The digital transformation of the Society 5.0 era has reshaped Generation Z's learning characteristics while simultaneously creating new challenges related to digital ethics in education. The rapid advancement of technology, particularly Artificial Intelligence (AI), social media, and digital platforms, requires Islamic Religious Education (PAI) not only to adapt to technological innovations but also to strengthen students' religious character and digital ethics. This study aims to analyze the transformation of Generation Z's learning characteristics, identify digital ethical issues in the Society 5.0 era, and reconstruct the instructional methodology of Islamic Religious Education through the development of the Netizen-Centered Learning conceptual model. This study employed a qualitative approach using the Narrative Literature Review (NLR) method by identifying, analyzing, evaluating, and synthesizing relevant scholarly literature on digital transformation in education, Artificial Intelligence, digital literacy, digital ethics, and Islamic Religious Education. The findings indicate that the transformation of Generation Z's learning characteristics requires a more interactive, collaborative, and student-centered learning approach. At the same time, technological advancement has generated various digital ethical issues, including cyberbullying, misinformation, hate speech, misuse of AI, academic plagiarism, and technology addiction. This study proposes the Netizen-Centered Learning conceptual model, which integrates digital technology development, Generation Z's learning characteristics, Islamic digital literacy, Qur'anic Communication, and digital religious character into a comprehensive Islamic Religious Education learning ecosystem. This model offers a conceptual contribution to the development of a more adaptive Islamic Religious Education methodology while maintaining Islamic values in the digital era.